PENINGKATAN PENGETAHUAN TENTANG PEMBERIAN ASI EKSKLUSIF PADA IBU MENYUSUI DI POSYANDU ANGGREK 3 LUBUK BAJA KOTA BATAM - Haqqelni Nur Rosyidah; Herviana Herviana; Nelli Roza; Norma Jeepi Margiyanti; Mawardi Badar (Nindikayla Institute, 2023)
Breast milk (ASI) is a source of meal that completed all the needs of infants aged 0-6 months. The nutritional content of breast milk has benefits in optimizing the growth and development of infants. The objectives of holding an extension program are: 1) Increased the knowledge of breastfeeding mothers about the importance of exclusive breastfeeding in infants aged 0-6 months. 2) Improved the skills of breastfeeding mothers about ASIP. 3) Improved the behavior of breastfeeding mothers towards exclusive breastfeeding to infants. Community service in this paper. The result of this counseling program is transfered knowledge to mothers regarding exclusive breastfeeding in infants aged 0-6 months